The Effectiveness of Goat Animal Manure as an Alternative Activator for Making Compost from Household Organic Waste - Navianti, Diah; Priyadi, Priyadi; Anwar, Khairil (Riviera Publishing, 2023)
This study examines the effectiveness of using goat manure activator in making compost from household organic waste. The type of research used was quasi-experimental, with pre-test and post-test control designs, and data were analyzed using the dependent T test to determine the effect of using goat manure activator on chemical parameters in compost and then analyzed again. with independent T-test to determine the effectiveness of manure activator. Animals with EM4 as control. Results of the study For chemical parameters the average moisture content was 2.07%, and the average NPK macro elements in compost with goat manure activator were each 0.46%. 0.45% and 0.76% of the results follow SNI 19-7030-2004 standards. While the average pH of 7.75 exceeds the maximum SNI standard of 7.49. In terms of physical parameters, the resulting compost has a temperature of 280C, is black in color, and has an earthy smell according to SNI. Statistical test results showed the effect of adding goat manure activator on the chemical and physical parameters of compost (p?0.05). Furthermore, the results of statistical tests obtained goat manure activator which is effectively used as an activator. The test results showed no difference in yield with control bioactivation (p?0.05) and had compost maturity according to SNI with two weeks composting time. Goat manure activator is very well used as an alternative activator in making compost from household organic waste.